Toxicity effect of expired pesticides to freshwater fish, Labeo rohita - Satyavani, G; Gopi, RA; Ayyappan, S; Balakrishnamurthy, P; Reddy, P Neelakanta (Journal of Agriculture and Environment, 2013)
We selected 15 widely used pesticide formulations to investigate possible chemical, biological and toxicological effects of expired pesticides that may enter into our ecosystem. They comprised of organophosphate and pyrethroid based insecticides, azole based fungicides, acetamide, propionate, acetic acid based herbicides, and fungicides mixtures containing two actives of azole and dithiocarbamates. The selected compounds were tested for acute toxicity to fish, Labeo rohita using Organisation for Economic Co-operation and Development (OECD) guideline no. 203 under static condition. Five to six concentrations (ranges from 0.005 – 80 mg/L) of both expired and unexpired pesticide formulations were tested along with controls under similar conditions at Department of Ecotoxicology, International Institute of Biotechnology and Toxicology. The results of the LC50 (Lethal Concentration)demonstrated significantly lower LC50 values for the expired pesticides as compared to the corresponding unexpired counter part. From this data, it is clear that expired pesticide formulations must be disposed carefully and, care should be taken to avoid their discharge to water bodies and thus prevent loss to fish. The Journal of Agriculture and Environment Vol:12, Jun.2011, Page 1-9 DOI: http://dx.doi.org/10.3126/aej.v12i0.7557